2015
DOI: 10.1109/jstars.2015.2457514
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Aircraft in Low-Resolution Multispectral Images: Specification of Relevant IR Wavelength Bands

Abstract: International audienceWe address the problem of detecting a stealth aircraft flying far away from an observer with limited visibility conditions using their multispectral signature. In such environment, the aircraft is a very low-contrast target, i.e. the target spectral signature may have a similar magnitude to the background clutter. Therefore, methods accounting only for the spectral features of the target, while leaving aside its spatial pattern, may either lead to poor detection statistics or high false a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…It can recognize camouflage in the presence of strong electronic interference. The infrared imaging system has strong detection and recognition ability for stealth aircraft, drones, and other hidden target or target under strong light interference, which is more suitable for high-precision observation than radar [10]. Meanwhile, the infrared imaging system can collaborate with radar and radio to fill the blind spot of radar [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…It can recognize camouflage in the presence of strong electronic interference. The infrared imaging system has strong detection and recognition ability for stealth aircraft, drones, and other hidden target or target under strong light interference, which is more suitable for high-precision observation than radar [10]. Meanwhile, the infrared imaging system can collaborate with radar and radio to fill the blind spot of radar [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nanoscale spectral resolution of HSIs also brings some problems, such as high computational complexity and redundant information [20]. In fact, there are a large number of redundant bands or low-SNR (signal-to-noise ratio) bands in HSIs, and some previous studies [21][22][23][24] have confirmed that the detection of specific target can be achieved with a small number of representative bands. As a result, dimensionality reduction (DR) is considered to be a necessary preprocessing step to remove the data redundancy for target detection.…”
Section: Introductionmentioning
confidence: 99%